INVESTIGATION OF SPECIAL ASYMMETRICAL MODES OF THREE-PHASE THREE-LEG AUTOTRANSFORMERS - Bosneaga V.A; Suslov V.M. (Problems of the Regional Energetics)
the base of earlier proposed model calculations were made and were investigated peculiarities of special asymmetric modes of three-phase three legs autotransformer (AT) with tertiary winding, connected in triangle. Calculations were carried out taking into account the electromagnetic coupling of coils, located on different legs. Modules and angles of currents and voltages vectors in autotransformer windings were calculated at breakage of one of the phases of the supply voltage and its simultaneous fault to ground at the side of AT. Based on these data vector diagrams were constructed, which give a visual representation of specific features of such regimes. Considered mode at grounded neutral is characterized by the occurrence of significant currents of the same value in all windings, app. equal to nominal current. Voltage of the windings varies slightly from the nominal values, except for the short-circuited phase. Furthermore, there is a considerable flow of the zero sequence flux, which may lead to additional heating of AT. At ungrounded neutral in this particular mode and absence of load on the secondary AT side, only a small magnetizing currents flows and neutral is significantly displaced. If the load is present, despite of the absence of the current in the neutral, currents in the windings, comparable with the nominal one appeared, also zero sequence flux appeared. In the general case, the currents of this failure (as in the previous case) are much smaller, than the usual short-circuit currents, so are insufficient to trigger the relay protection, this may require additional measures to protect AT against such damage.